(untitled) (Baghdad Science Journal, 2021)
Bimetallic Au –Pt catalysts supporting TiO2 were synthesised using two methods; sol immobilization and impregnation methods. The prepared catalyst underwent a thermal treatment process at 400◦ C, while the reduction reaction under the same condition was done and the obtained catalysts were identified with transmission electron microscopy (TEM) and energy-dispersive spectroscopy (EDS). It has been found that the prepared catalysts have a dimension around 2.5 nm and the particles have uniform orders leading to high dispersion of platinum molecules .The prepared catalysts have been examined as efficient photocatalysts to degrade the Crystal violet dye under UV-light. The optimum values of Bimetallic Au –Pt catalysts supporting TiO2 have been found (0.05g of the catalyst prepared in sol immobilization method, 0.07 g of the synthesised in impregnation procedure. The impact of pH on the degradation reaction was tested; it has been found that pH 10 is the best media for the reaction. The effect of temperature has been discussed when various temperatures were used, and the heat of photoreaction Ea was estimated from the Arrhenius relationship, it has been concluded that the reaction is independent of temperature as the activation energy was very small (Ea= 22 kJ/ mole). The thermodynamic functions; entropy, enthalpy and the free energy have been figured out. It has been found that the positive values of enthalpy ∆H# refer to endothermic reaction, moreover, it has been demonstrated that the photoreaction is an endergonic one according to the calculated values of the free energy of activation. It has been noticed that when temperature increases, it promotes the production of free radicals, but it has been noticed that exceeding the temperature more than the used range causes reducing the percentage of degradation of crystal violet, the reason is due to the limitation conditions of adsorption process at higher temperature on the surface of the catalyst.